Eksplorasi Fenomena Indoglish Dalam Lanskap Linguistik Media Publik Di Distrik Manokwari Barat - Yulia Putri Paradida; Estiani Ambarwati (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to identify and classify the forms of Indoglish that appear in public media spaces such as banners, billboards, shop signs, and advertisements, encompassing lexical elements in the form of words, phrases, clauses, and sentences combining Indonesian and English. In addition, the study analyzes the functions and social meanings of Indoglish usage by examining the social, economic, and cultural motives and representations of identity, power, and ideology of space owners. The method employed is descriptive qualitative with a text analysis approach to explore linguistic phenomena within the linguistic landscape of West Manokwari District. The researcher collected data through direct field documentation techniques, photographing linguistic objects in the research area. The results reveal various Indoglish forms in the public media linguistic landscape, including word, phrase, clause, and sentence level instances. Furthermore, all analyzed data reflect the six functions of language proposed by Roman Jakobson and carry social meanings that represent particular identities, power relations, and ideologies in the public space.